2012
DOI: 10.1055/s-0031-1291664
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess mediastinal emphysema after esophageal endoscopic submucosal dissection with carbon dioxide insufflation

Abstract: Whereas mediastinal emphysema detected by radiography is not so common, MDCT immediately after ESD revealed a certain prevalence of post-ESD mediastinal emphysema. Insufflation of CO2 rather than air during esophageal ESD significantly reduced postprocedural mediastinal emphysema. CO2 can be considered as insufflating gas for esophageal ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 7 publications
0
48
2
1
Order By: Relevance
“…Based on the results of a pilot study [8] , the incidence of ME with air insufflation was 63% and that of CO2 was 30%. To detect this difference with a power of 0.7 and alpha of 0.05, 22 patients per group would be required.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the results of a pilot study [8] , the incidence of ME with air insufflation was 63% and that of CO2 was 30%. To detect this difference with a power of 0.7 and alpha of 0.05, 22 patients per group would be required.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, CO2 insufflation during diagnostic or therapeutic endoscopy has been shown to be safe and effective in reducing procedure-related pain and discomfort [1][2][3][4][5] . The safety of CO2 insufflation for endoscopic submucosal dissection (ESD) has also been shown in several studies [6][7][8] . As for esophageal ESD, it is known that mediastinal emphysema (ME) can develop even if no perforation is recognized during or at the end of the procedure because the esophagus has no serosa [9][10][11] .…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations